Pengenalan Manajemen Sederhana Pada Petani Usaha Lengkuas (Studi kasus di Desa Ulak Lebar Kecamatan Merigi kelindang Kabupaten Bengkulu Tengah) - Prawitasari, Andriyani; Junaidah, Junaidah; Ahwat, Dadang Utuh; Sari, Anita (Universitas Dehasen Bengkulu, 2022)
One of the weaknesses of farmers in Indonesia is related to the problem of managing their farms. Farmers usually carry out activities as part of daily life so that the management or management process is not passed properly, starting from the planning, organizing, implementing, and controlling stages of the business. Likewise with the farmers in the village of Ulak Lebar kec. Merigi Kelindang Kab. Central Bengkulu. With this background, this service activity was carried out. Using a simple management introduction method, it can measure changes in both the knowledge and management skills aspects to the community. After participating in the socialization, the community's knowledge increased along with their understanding of the management function (POAC).